ANALISIS PERBANDINGAN PEMIKIRAN JOHN DEWEY (PROGRESIVISME) DAN MOHAMMAD NATSIR (REVOLUSI PENDIDIKAN) DALAM KONTEKS PENDIDIKAN SD AL AZHAR BANDUNG - Nur Syifa, Nahdli Muhammad (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
Education is the main foundation in the formation of character and progress of a nation. It has been widely recognized by thinkers and educational figures throughout history. Two figures who have significant thoughts in the context of education are John Dewey, who is known as a figure of progressivism, and Mohammad Natsir, who carries the concept of educational revolution. These two concepts have different characteristics and approaches in looking at education, but both have the same goal, which is to improve the quality of education for the betterment of individuals and society. The purpose of this study is to conduct a meta-analysis related to the thoughts of the two figures. This paper focuses on the thoughts of John Dewey (progressivism) and Mohammad Natsir (educational revolution) in the Educational Context of SD Al Azhar Bandung. The method used in this study is a qualitative method with a descriptive type of analysis. The results of this study show that in the context of SD Al Azhar Bandung Education, the thoughts of John Dewey and Mohammad Natsir can be harmoniously integrated to create a learning environment that is student-centered, value-oriented, and strives to create positive changes in society. Thus, education at SD Al Azhar Bandung can be a vehicle to build a generation that is intelligent, critical, and morally responsible in facing the challenges of the times. integration of thought between John Dewey (Progressivism) and Mohammad Natsir (Education Revolution) at SD Al Azhar Bandung. This shows that education at SD Al Azhar Bandung has succeeded in creating a conducive and supportive learning environment for the holistic growth of students, who are not only academically intelligent, but also ethical and culturedTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//